SISTEM INFORMASI INVENTORY STOK BARANG PADA WAHANA BOOK BERBASIS WEBSITE - Rama Aldiansyah Ramadhan (2023)
The process of globalization is developing rapidly and has a significant impact on our lives. The development and growth of technology plays a central role in the activities of individuals and companies. The existence of technology can increase work efficiency and facilitate. Currently, Wahana Book still uses conventional methods of managing and reporting goods. The process involves directly inputting goods and reporting that is recorded in the general ledger. To facilitate the work process at Wahana Book, the authors designed a stock inventory information system using a website-based platform. In designing this study the authors used the waterfall method for the planning process to run sequentially from the problem identification stage to the system testing stage, when conducting system analysis the authors used the PIECES method. The device system is designed using the PHP programming language with MYSQL as a database management system. With the presence of this application system, Wahana Book can make it easier to collect data on goods, store data on goods, and print reports on incoming and outgoing goods in a computerized manner